Multikulturalisme Sebagai Identitas Kolektif, Kebijakan Politik dan Realitas Sosial - Arie Setyaningrum (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2003)
The article offers an elaborate discussion on multiculturalism as collective identity, state (or public) policy and social fact. As a collective identity, multiculturalism implicates to diversity in cultural practices and how this cultural construct contribute to social and political process which in turn affect state policy formulation. As a policy, multiculturalism is a form of protectionist policy to maintain diversity in collective identity within a nation-state. As a social fact, multiculturalism is adoption of cultural and social diversity in day to day life. The article endeavors further chances of multiculturalism as an ideology becoming a national identity within the sphere of state policy. However, practices of multicultural policies, as argued here, are often disguised by a form of cultural hegemony as there are discriminatory political practices toward certain ethnic groups.